Effect of Acupressure Seven Meridian Points on Blood Pressure Changes in Hypertensive Patients - Gede, Budi Widiarta; Martini, Made; Ernayanti, Ni Luh Putu (Babali Nursing Research, 2023)
Background: hypertension is a disease in which blood pressure occurs. So that it can affect the occurrence of physical changes and psychological changes. Acupressure therapy has an important role in overcoming physical conditions, including changes in blood pressure. Acupressure therapy is carried out by giving massage to acupuncture points and can have a relaxing effect on the patient. Objective: This study was conducted to examine the effect of acupressure therapy on reducing blood pressure in hypertension sufferers in the Work Area of the State Health Center (Puskesmas II Negara). Methods: This research is quantitative research with Pre-Experimental with One Group Pretest Posttest Design. The sample of this study was 30 hypertension sufferers using a purposive sampling technique. The data collection tool used was a patient observation sheet given Acupressure Therapy at 7 meridian points (ST 9, PC 6, ST 36, LI 4, DU 16, GB 20, and GB 21 points) Results: The effect of acupressure therapy on blood pressure was analyzed with the Wilcoxon test because the data is not normally distributed. The Wilcoxon test shows a p-value of 0.000 with a predetermined significance, namely α (0.05), so the p-value <0.05 indicates an influence. Conclusion: This shows that there is an effect of acupressure therapy on blood pressure in hypertensive patients in the working area of the State Health Center (Puskesmas II Negara).